A Textbook Analysis of “English in Context SMP/MTs Grade VIII” Based on Its Content and Technical Qualities - Erica Indriyani; Amalia Nurhasanah (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2017)
The aims of this article were to uncover the detailed content of an English textbook entitled “English in Context SMP/MTs Grade VIII” for Junior high school students as well as to investigate the technical quality of the book. The design of the research was a descriptive qualitative through which the English textbook entitled “English in Context SMP/MTs Grade VIII” written by Kasihani K.E. Suyanto and Sri Andreani was assessed. The book was read, identified, classified, and analyzed in terms of its content and technical quality. The findings were: 1) the book was sufficient in terms of the content because total score of the alignment between its content and curriculum was thirty-three (33), 2) in terms of technical quality, this book is sufficient within evidence of a total score which was thirty (30). Based on the data analysis above the writers concluded that an English textbook entitled “English in Context for Grade VIII” is good and appropriate for teaching English to the second grade students of Junior high school.